Ionization and electron capture in collisions of bare carbon ions with hydrogen - Abdurakhmanov, Ilkhom; Massen-Hane, K.; Alladustov, S.; Bailey, J.; Kadyrov, Alisher; Bray, Igor (2018)
Ionization and electron capture in collisions of bare carbon ions with atomic hydrogen has been studied using the wave-packet continuum discretization approach. The three-body Schrödinger equation governing the collision process is solved using the two-center expansion of the total scattering wave function. Calculations have been performed for the projectile energy range from 1 keV/amu to 10 MeV/amu. While there is excellent agreement with experimental data for the total electron-capture cross section over the entire energy range, the calculated total ionization cross section slightly overestimates the only available measured point. The singly and doubly differential ionization cross sections at 1 and 2.5 MeV/amu are in good agreement with experiment. The differential cross section calculations are extended to lower energies where perturbative methods are expected to fail. At 100 keV/amu impact energy the present singly differential cross section in the ejected angle of the electron shows a pronounced peak in the forward direction. It is concluded that at low incident energies electron capture into the continuum of the projectile strongly enhances electron ejection in the forward direction.